Oxy hóa cao su thiên nhiên và pha chế Vec-ni - Ninh, Phan Văn; Cường, Ngô Duy; Tính, Vũ Văn; Định, Lê Văn; Hạnh, Phó Đức (VNU Journal of Science: Natural Sciences and Technology; Vol 1 No 3, 1985)
Abstract